Innovation centres as anchor spaces of the 'knowledge city'. (6th March 2019) - Morisson, Arnault
Since the late 2000s, collaborative spaces have been emerging in post-industrial cities around the world. A recent trend in collaborative spaces is the concept of the innovation centre. The paper defines innovation centres and investigates their role in the making of the knowledge city. The research methodology uses a multiple case study in which three cases were selected: Barcelona Growth Centre in Barcelona (Spain), Ruta N in Medellin (Colombia), and Station F in Paris (France). The case studies were selected for the purpose of generalising findings about the concept of an innovation centre. Innovation centres are collaborative spaces that cluster diverse knowledge-based actors, namely private companies, entrepreneurs, public institutions, and universities, within the same building. Innovation centres provide a wide range of amenities in order support face-to-face interactions and the spread of tacit knowledge. This paper finds that innovation centres are initiatives that participate in the making of the knowledge city.